(untitled) - Said, Edward W. (New York, 1979)
In this wide-ranging, intellectually vigorous study, Said traces the origins of "orientalism" to the centuries-long period during which Europe dominated the Middle and Near East and, from its position of power, defined "the orient" simply as "other than" the occident. This entrenched view continues to dominate western ideas and, because it does not allow the East to represent itself, prevents true understanding. Essential, and still eye-opening, Orientalism remains one of the most important books written about our divided world.
Keywords: Chủ nghĩa Phương Đông,Orientalism